Rural settlement schemes in the South West of Western Australia and Roraima State, Brazil: Unsustainable rural systems? - Jones, Roy; Diniz, A.; John Selwood, H.; Brayshay, M.; Lacerda, E. (NORTH UNIV BAIA MARE, 2015)
In the years after the First World War, the British and Western Australian governments cooperated in a Group Settlement Scheme. Its aim was to bring groups of settlers from various locations in the United Kingdom to remote forested parts of the South West of Western Australia, and to supply them with tools, building materials and livestock with which they were to clear land and establish small farms. Successful settlers would then be granted ownership of the land that they had developed. The scheme met with limited success for a range of reasons including the challenging nature of the terrain and the vegetation, the unfamiliarity of the settlers with both farming and the local environment and the decline in economic opportunities resulting from the onset of the Great Depression. While many, if not most, settlers abandoned their farms within a relatively short period of time, some did develop successful dairy farms which have now been passed through several generations of family farmers for almost a century. Furthermore, many of the lots that were abandoned by the original Group Settlers during the depression have been reoccupied and redeveloped in recent decades as the scenic South West region has become a high amenity rural area characterised by growth in viticulture, tourism, retirement migration, hobby farming and telecommuting. This paper uses archival material to document the challenges and shortcomings of the original settlement scheme and will outline the subsequent development of some of the Group Settlement localities over the intervening decades. This experience is compared with the Nova Amazonia project, a modern day rural settlement scheme in a remote part of Brazil where the settlers have experienced challenges and difficulties comparable to those of the Group Settlers on an Australian frontier in the 1920s.